Building Character, Responsibility and Discipline in Online Learning for Universitas NU Pasuruan Students Majoring Physic Education - Siti Maimuna; Rohmatus Sholihah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study aims to determine the level of effectiveness of online learning physics courses in universities. This research is a literature study by taking references from several journals and library sources with a narrative presentation to see the effectiveness of online learning in universities. As educators, lecturers utilize various learning media and digital applications which are expected to be integrated into the student learning experience and still refer to learning outcomes in the semester learning plan (RPS). Physics is a compulsory subject. Online learning in physics courses at universities is indeed quit good, but has obstacles to understanding the physics material taught by lecturers, including the learning provided is more dominant in theory and practicum activities are not optimally implemented. So that the effectiveness of online learning of physics courses in universities can be categorized as quite effective because the results are not optimal.